2013
DOI: 10.1248/bpb.b13-00231
|View full text |Cite
|
Sign up to set email alerts
|

Selective Androgen Receptor Modulator, YK11, Regulates Myogenic Differentiation of C2C12 Myoblasts by Follistatin Expression

Abstract: The myogenic differentiation of C2C12 myoblast cells is induced by the novel androgen receptor (AR) partial agonist, (17α,20E)-17,20-[(1-methoxyethylidene)bis-(oxy)]-3-oxo-19-norpregna-4,20-diene-21-carboxylic acid methyl ester (YK11), as well as by dihydrotestosterone (DHT). YK11 is a selective androgen receptor modulator (SARM), which activates AR without the N/C interaction. In this study, we further investigated the mechanism by which YK11 induces myogenic differentiation of C2C12 cells. The induction of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…This compound has a partial agonistic effect on AR compared to dihydrotestosterone (DHT) as determined by a reporter gene assay. 24) Furthermore, we found that YK11 accelerates myogenic differentiation in C2C12 myoblast cells. 25) The present study focus on the bone anabolic effect of YK11 on osteoblastic differentiation.…”
mentioning
confidence: 70%
“…This compound has a partial agonistic effect on AR compared to dihydrotestosterone (DHT) as determined by a reporter gene assay. 24) Furthermore, we found that YK11 accelerates myogenic differentiation in C2C12 myoblast cells. 25) The present study focus on the bone anabolic effect of YK11 on osteoblastic differentiation.…”
mentioning
confidence: 70%
“…In mouse and chick, FST functions as a positive regulator of muscle development and growth by inhibiting TGF-␤ family members including myostatin (2,23,34,43,64). As to cellular behavior, FST regulates the proliferation (4,7,23,35), differentiation (4,32), and fusion (29) of muscle cells in myogenesis in vivo and in vitro of mouse and duck. The present evidence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of neither IGF-1 isoform, however, was significantly impacted by tumor or treatment (Supplemental Figure 5). Myostatin signaling also governs skeletal muscle mass and is another target of androgens as myostatin, its receptor ACVRIIB, and the negative regulator of myostatin, follistatin, have all been shown to be androgen-regulated [35,53,54]. ACVRIIB was induced by the presence of C-26 tumors and was significantly suppressed only by AR-42 treatment, alone or in combination with GTx-024 ( Figure 4D).…”
Section: Impact Of Gtx-024 and Ar-42 Administration On Androgen Recepmentioning
confidence: 98%